CHALLENGING THE PALATE AND THE MIND. INTRODUCING WESTERN BAKING VOCABULARY INTO CHINESE - ZLOTEA, Mugur (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Challenging the Palate and the Mind. Introducing Western Baking Vocabulary into Chinese. Starting from the first Western recipe book published in China in 1866, the paper analyzes the attempts to translate Western bakery vocabulary into Chinese. Although the Chinese cuisine was already very rich and refined, with a complex vocabulary, dessert had never been an integral part of a traditional meal, and, in fact, there was no specific word for it. After China’s defeat in the two Opium Wars, in the mid-19th century, the increasing foreign presence on Chinese soil meant both an increase in demand for cooks able to satisfy the dietary needs of the Westerners, and of restaurants serving Western food, especially in cities with foreign concessions, like Shanghai, where dining in such a place had become very “modern”. Zao yang fan shu (Foreign Cookery in Chinese) compiled and translated by Martha Foster Crawford, and published at The American Presbyterian Mission Press, in Shanghai, in 1866, was the first Western recipe book to be translated into Chinese. Out of the 271 recipes, 139 are desserts. Considering the resistance of the Chinese language to loanwords, especially phonetic loans, the paper looks at the solutions employed by Crawford to translate the new vocabulary, find out when were the phonetic loans used and how were they transcribed, if it was possible to identify equivalents in Chinese for the new terms, which terms were translated as semantic loans, and which are still in use today. Provocarea gustului și a minții. Pătrunderea vocabularului de patiserie occidentală în China. Pornind de la prima carte de bucate occidentale publicată în China în 1866, lucrarea de față propune o analiză a transpunerii vocabularului patiseriei occidentale în limba chineză. Deși în momentul publicării cărții, bucătăria chineză era deja extrem de bogată și rafinată, cu un vocabular complex, desertul nu era parte dintr-o masă tradițională și nu exista un termen care să definească acest fel. După înfrângerea Chinei în cele două Războaie ale opiului, prezența tot mai numeroasă a occidentalilor pe teritoriul chinez a făcut ca cererea de bucătari capabili să satisfacă cerințele culinare ale străinilor și numărul restaurantelor care serveau mâncare occidentală să crească, mai ales în orașele cu concesiuni străine, precum Shanghai, unde servitul mesei în restaurante occidentalizate devenise o modă. Prima carte de bucate occidentale în limba chineză, Zao yang fan shu (Rețete occidentale în chineză), a fost tradusă și editată de Martha Foster Crawford, în 1866, publicată la Editura Misiunii Prezbiteriene Americane, din Shanghai. Dintre cele 271 de rețete, 139 sunt deserturi. Luând în considerare rezistența limbii chineze la împrumuturi, mai ales la cele fonetice, lucrarea de față analizează soluțiile folosite de Crawford pentru a reda în chineză vocabularul de patiserie, când și de ce au fost preferate calcurile fonetice, cum au fost ele transcrise, dacă a fost posibilă identificarea unor termeni echivalenți din vocabularul culinar chinez pentru felurile de desert incluse în carte, când s-a folosit calcul semantic și care dintre termenii propuși de autoare mai sunt încă în uz. Cuvinte-cheie: Zao yang fan shu, traducere, carte de bucate, patiserie, împrumuturi fonetice/semantice Article history: Received 22 August 2023; Revised 03 January 2024; Accepted 17 January 2024; Available online 27 March 2024; Available print 27 March 2024